(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2020)
Makyung is one of the many traditional performances from the Malaysian region that has shaped the Malay national cultural identity. It has been recognized as one of the Masterpieces of the Oral and Intangibles of Humanity in 2001 as well as part of intangible cultural heritage having significant cultural values propounded by the UNESCO International Convention for the Safeguarding of Intangible Cultural Heritage of 2003 (ICH Convention). However, the State of Kelantan had enacted the Entertainment Control and Places of Entertainment Enactment (1998) (KECE 1998) that clearly prohibits any entertainment containing prohibited elements according to Islamic principles. Currently, the performance of makyung was allowed with certain modifications but recently, there is an intention by the state government of Kelantan to prohibit Makyung totally. It is to be noted that there are overlapping powers between the Federal and the State jurisdictions with regard to the safeguarding of makyung. At federal level, the National Heritage Act 2005 (the NHA) is the existing law in Malaysia for the safeguarding of intangible cultural heritage inspired by the establishment of the ICH Convention. However, the NHA is a general law that is inadequate at giving comprehensive protection to makyung since heritage matter falls under the Concurrent List of the Ninth Schedule of the Federal Constitution where the State also has the legislative power to make law with regard to the same. In order to address this conflict, there is a need to examine the provisions in the Federal Constitutions, the NHA, KECE 1998 and evaluate to what extent these laws safeguard the performance of makyung. This study examines the conflicts in powers between both Federal and the State Legislations which powers are guaranteed by the Constitution. This study uses the qualitative research method, where a doctrinal research is conducted. This paper contends that, both powers must come to a compromise and meet halfway for the preservation of the heritage. Keywords: Makyung, federal, state, intangible cultural heritage, law